Two new species of Schistidium (Grimmiaceae, Bryophyta) from western North America - Mcintosh, Terry; Blom, Hans H.; Toren, David R.; Shevock, James R. (Phytotaxa, 2015)
Schistidium splendens and Schistidium squarrosum are described as new species from western North America. Schistidium splendens is characterized mainly by 2-stratose striae in the distal leaf laminae, thick and strongly recurved leaf margins, relatively short awns, and more or less isodiametric or short-elongate, irregularly shaped exothecial cells. Schistidium squarrosum is characterized by often abruptly narrowed, ovate-lanceolate, usually curved or falcate leaves that often lack awns, 2(–3) stratose upper leaf laminae, and large, broadly ovate-lanceolate or lanceolate perichaetial leaves that tightly surround the capsule.